2013
DOI: 10.1111/j.1467-8543.2012.00909.x
|View full text |Cite
|
Sign up to set email alerts
|

Union Membership and Job‐Related Training: Incidence, Transferability, and Efficacy

Abstract: This study examines the relationship between union membership and (i) the incidence of training, (ii) the degree to which training is transferable to firms other than the one providing the training and (iii) the degree to which workers perceive that training improves job performance. Using data from the Australian Bureau of Statistics, I find that union members are more likely to receive employer‐sponsored training than their non‐union counterparts. I also find that male union members are more likely than non‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 36 publications
(78 reference statements)
0
30
0
Order By: Relevance
“…The data showed that employees who are satisfied were more likely to be unionized than those who are unionized. This seems to suggest that unionized employees were satisfied because unions negotiated for better training opportunities (Waddoups, 2014), fair and equitable policy, and a living or decent wage (Mmolaeng & Bussin, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data showed that employees who are satisfied were more likely to be unionized than those who are unionized. This seems to suggest that unionized employees were satisfied because unions negotiated for better training opportunities (Waddoups, 2014), fair and equitable policy, and a living or decent wage (Mmolaeng & Bussin, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…An international study revealed that unionized employees in low economic countries are satisfied, it negotiated for good working conditions (Charman & Owen, 2014). Union members are more likely to be satisfied than non-unionized members because they receive company benefits, for example training opportunities (Waddoups, 2014), fair and equitable policy, and negotiating a living wage (Mmolaeng & Bussin, 2012;Tufail et al, 2016). Conversely, studies conducted in the late 1970s showed that employees who were unionized were more dissatisfied compared to non-unionized employees (Borjas, 1979;Freeman, 1979).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of influential studies have established a link between unions and a pay premium and/or lower pay inequality (see, for example, Freeman 1980, Booth 1995, Gosling and Machin 1995, Clark and Oswald 1996, Card 1996, Card et al 2003, Budd and Na 2000, Metcalf et al 2001, Hirsch 2004, Blanchflower and Bryson 2004. Unions have also been linked to a number of other welfare improving changes for members, which include access to employer provided training (Booth 1991, Acemoglu et al 2001, Booth et al 2003, Waddoups 2012, risk sharing (Malcomson 1983), health insurance and pension plans (Buchmueller et al 2002), workplace and occupational health and safety (Donado and Walde 2012), family friendly policies (Budd and Mumford 2004), and curbing discrimination (Phanindra and Peled 1999). More generally, unions uphold members' interest in collective bargaining on issues such as transfers, promotions and grievances, among others, in the spirit of Freeman and Medoff (1984)'s "collective voice".…”
Section: Review Of the Literaturementioning
confidence: 99%
“…This article examines the relationship between employee representatives and firm-level continuing vocational training (CVT). Studies have shown that employees are more likely to receive CVT in firms with works councils or a trade union presence (Böheim and Booth, 2004; Booth et al, 2003; Cantner et al, 2014; Green et al, 1999; Heyes and Stuart, 1998; Leisink and Greenwood, 2007; Stegmaier, 2012; Waddoups, 2014). Hoque and Bacon (2008) found greater equality of training provisions for different groups of employees in unionized firms that had learning representatives.…”
Section: Introductionmentioning
confidence: 99%